Acute exacerbation of interstitial lung disease as a sequela of COVID-19 pneumonia (2020)
Interstitial lung disease (ILD) is a heterogeneous group of disorders characterized by dyspnea and bilateral infiltrations of the lung. While some cases are idiopathic (e.g., idiopathic pulmonary fibrosis), others are associated with systemic illnesses (e.g., autoimmune disorders), environmental exposures (e.g., asbestosis, hypersensitivity pneumonitis), or drug-induced, among other causes 1 . In general, ILD results from inflammation and excessive accumulation of connective tissue matrices in the interstitium of the lung 2 . Exacerbations with rapid progression resulting in increased dyspnea, increased oxygen supplementation requirements, and respiratory failure have been described in idiopathic pulmonary fibrosis and other types of ILDs 3 . Surgery, aspiration of gastric contents, infection, and other factors have been proposed to contribute to ILD exacerbation. Viral infection has been implicated as an important cause of ILD and of ILD exacerbation, but the viruses involved and the mechanisms triggered during an exacerbation remain poorly elucidated 4 . Recent concerns have been raised by the potential impact of the COVID-19 pandemic on ILD, mainly because of its propensity to cause severe lung injury in older individuals and in individuals with pre-existing lung disease. COVID-19 is caused by the novel  coronavirus SARS-CoV-2. 5 Here, we present a case of a patient with Rheumatoid Arthritis (RA) associated ILD (RA-ILD) recently hospitalized due to COVID-19. We first summarize the case and discuss the literature followed by a discussion of gaps in knowledge in need of further investigation.